Peningkatan Keterampilan Membaca Permulaan pada Pembelajaran Tematik dengan Metode Suku Kata Kelas 1 MI Al Islamiyah Kota Tegal - Gagas Pamulyo Aji Gagas; Trikinasih Handayani; Dewi Partini (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2022)
This study aims to determine the improvement of students' initial reading skills in using the syllable method for class 1 Mi Al Islamiyah. This research was conducted using two cycles, and each cycle consisted of two meetings. The research subjects were 23 students, including 13 male students and 10 female students. The object of this research is the application of early reading skills. Data collection techniques in the form of tests, documentation and. The data analysis used is qualitative and quantitative analysis.The results of this study indicate that the application of the syllable method can improve students' initial reading skills. Students who get a complete reading skill score in the pre-cycle are 57% (10 students). In the first cycle the average value of the students who completed was 68 with a percentage of completeness as much as 65% (15 students), while in the second cycle the average value of the students who completed was 76.3 with the percentage of completeness 83% (19 students). It can be concluded that the syllable method can improve early reading skills, thus the researcher's suggestions for teachers should apply the syllable method in early reading skills